Participation of cardiac thelocytes in the formation and protection of myocardial blood microscope in the process of early postnatal development of Wistar rats - Zagoruiko , G.E.; Martsinovsky , V.P.; Filatova , V.L.; Matvienko , T.M.; Filatova , O.V.; Sargosh , O.D. (Морфологія / Morphologia / Morfologìâ, 2026)
Relevance. In recent years, active studies of the participation of telocytes in prenatal and postnatal angiogenesis of mammals have been observed. Despite certain successes in studying the ultrastructure and function of cardiac telocytes, the processes of formation of interactions "telocyte ↔ endothelial cell", "telocyte ↔ smooth muscle cell", which contribute to the postnatal development of the capillary network, arterioles, venules of the myocardium of the left ventricle of Wistar rats, remain poorly studied. Purpose. To investigate the interactions of telocytes and their processes with capillary endothelial cells and myocardial arteriolar smooth muscle cells during the early postnatal development of Wistar rats. Methods. Using electron microscopy, a series of ultrathin sections of the left ventricular myocardium of Wistar rats at the age of 5, 10, 15 and 45 days of postnatal development were studied. Results and summary. It was established that during the first 15 days of postnatal development of rats, an increase in the number and size of telocytes and their processes occurs in the stromal-vascular component of the myocardium. Telocytes with processes are found near the blood capillaries. After some time, the processes of telocytes surround the blood capillaries and form contacts with endothelial cells "telocyte ↔ endotheliocyte". In the time interval (5-15) days, the number of protrusions and the number of microvilli on the lumenal surface of the capillary endothelium significantly increases. This leads to a significant increase in the area of ​​the lumenal surface of endothelial cells. Within 15 days after the birth of rats, a kind of protective shell of several layers of telocyte processes is formed around some arterioles in the myocardium of the left ventricle. But in the time interval (15-45) days, the reverse process is observed in the stromal-vascular component of the myocardium: the number of telocytes and their processes decreases; the area of ​​the ablumenal surface cytolemma of the capillary endothelium increases due to the directed migration and fusion with the plasmalemma of numerous cytoplasmic microvesicles; the protective shell of cardiac telocyte processes around the arterioles “disappears”. The obtained data convincingly indicate that cardiac telocytes and their numerous processes participate in the development of intercellular communication and contribute to the integrity of the ultrastructure of blood microvessels. Thus, the shell of telopods protects the network of the myocardial microcirculatory bed from possible damage and for some time prevents the increase in the diameter of microvessels.